(3GdJPcQI (B( (3aj abg GdRjOjI(B)s - (3GdMSf Hf eMeO Hf GdMSf Hf SGHb GdOjf, GHf jYjT GdUfYGfj,J (B791 (3g` s
(3ChdgG (B:s
(3jZjQ ChUGag Ch HYVgG hRYaQGf hcGahQ heGA hQO aUd GfeG jLhR GdhVhA hGdZSd HGdeGA GdMdGd s
(3BNQgG (B:s
(3aEf cGf CgdgG CQHYjf aeGJ HYV GdeNJGQjf ddJcQjQ GSJHOdhG HOdge s
(3GdfSNI HgG MhGTs
(3bO CKfi GdThcGfi ai GdHOQ GdWGdY Ydi gPG GdcJGHs
(3fSN GdLRA GdChd SfI (B794 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B216 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B280s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis